Shear Stress-Induced Alteration of Epithelial Organization in Human Renal Tubular Cells. - Damien Maggiorani (PLoS ONE, 2015)
Tubular epithelial cells in the kidney are continuously exposed to urinary fluid shear stress (FSS) generated by urine movement and recent in vitro studies suggest that changes of FSS could contribute to kidney injury. However it is unclear whether FSS alters the epithelial characteristics of the renal tubule. Here, we evaluated in vitro and in vivo the influence of FSS on epithelial characteristics of renal proximal tubular cells taking the organization of junctional complexes and the presence of the primary cilium as markers of epithelial phenotype. Human tubular cells (HK-2) were subjected to FSS (0.5 Pa) for 48 h. Control cells were maintained under static conditions. Markers of tight junctions (Claudin-2, ZO-1), Par polarity complex (Pard6), adherens junctions (E-Cadherin, β-Catenin) and the primary cilium (α-acetylated Tubulin) were analysed by quantitative PCR, Western blot or immunocytochemistry. In response to FSS, Claudin-2 disappeared and ZO-1 displayed punctuated and discontinuous staining in the plasma membrane. Expression of Pard6 was also decreased. Moreover, E-Cadherin abundance was decreased, while its major repressors Snail1 and Snail2 were overexpressed, and β-Catenin staining was disrupted along the cell periphery. Finally, FSS subjected-cells exhibited disappeared primary cilium. Results were confirmed in vivo in a uninephrectomy (8 months) mouse model where increased FSS induced by adaptive hyperfiltration in remnant kidney was accompanied by both decreased epithelial gene expression including ZO-1, E-cadherin and β-Catenin and disappearance of tubular cilia. In conclusion, these results show that proximal tubular cells lose an important number of their epithelial characteristics after long term exposure to FSS both in vitro and in vivo. Thus, the changes in urinary FSS associated with nephropathies should be considered as potential insults for tubular cells leading to disorganization of the tubular epithelium.